2010
DOI: 10.1521/aeap.2010.22.3.184
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Mapping as a Participatory Approach to Developing an HIV Prevention Intervention in Rural African American Communities

Abstract: Southeastern states are among the hardest hit by the HIV epidemic in this country, and racial disparities in HIV rates are high in this region. This is particularly true in our communities of interest in rural eastern North Carolina. Although most recent efforts to prevent HIV attempt to address multiple contributing factors, we have found few multilevel HIV interventions that have been developed, tailored or tested in rural communities for African Americans. We describe how Project GRACE integrated Interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 59 publications
0
56
0
Order By: Relevance
“…TORO was developed through Project GRACE (Growing, Reaching, Advocating for Change, and Empowerment), a community-based participatory research partnership in rural North Carolina (Corbie-Smith et al, 2010). Other published papers describe partnership development (Corbie-Smith et al, 2011), the content and structure of the intervention (Corbie-Smith et al, 2010), as well as the initial process evaluation (Albritton et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TORO was developed through Project GRACE (Growing, Reaching, Advocating for Change, and Empowerment), a community-based participatory research partnership in rural North Carolina (Corbie-Smith et al, 2010). Other published papers describe partnership development (Corbie-Smith et al, 2011), the content and structure of the intervention (Corbie-Smith et al, 2010), as well as the initial process evaluation (Albritton et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Other published papers describe partnership development (Corbie-Smith et al, 2011), the content and structure of the intervention (Corbie-Smith et al, 2010), as well as the initial process evaluation (Albritton et al, 2014). In brief, the program used a LHA model, in which community members considered natural helpers are trained to share their new knowledge and skills with friends to achieve targeted improvements in behavioral determinants (e.g., attitudes, normative beliefs, and self-efficacy).…”
Section: Methodsmentioning
confidence: 99%
“…This study utilized baseline data from Teach One Reach One, a risk-reduction intervention that used community-based participatory research methods to train African American early adolescents and their caregivers to disseminate information concerning caregiver-adolescent communication about sex, and adolescent sexual and relationship health and well-being within their social networks (Corbie-Smith et al, 2011; Corbie-Smith et al, 2010; Ritchwood et al, 2015). We recruited participants between 2008 and 2009 who resided in one of five rural counties in eastern North Carolina that shared similar socio-demographic and socio-economic statuses.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were offered an incentive of $30 USD. Additional details about study procedures have been detailed elsewhere (Corbie-Smith et al, 2011; Corbie-Smith et al, 2010; Dave et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Although southeastern states tend to have the highest rates of syphilis and other STIs in the United States (CDC, 2011d;Corbie-Smith et al, 2010), the some of the highest proportions of abstinence-only policies are found in southeastern states (54%) (e.g., Florida, Georgia, etc. ),…”
Section: Sex Education Policy and Federal Fundingmentioning
confidence: 99%